Metabolic and molecular responses to leucine‐enriched branched chain amino acid supplementation in the skeletal muscle of alcoholic cirrhosis. Issue 6 (27th February 2015) - Tsien, Cynthia; Davuluri, Gangarao; Singh, Dharmvir; Allawy, Allawy; Ten Have, Gabriella A.M.; Thapaliya, Samjhana; Schulze, John M.; Barnes, David; McCullough, Arthur J.; Engelen, Marielle P.K.J.; Deutz, Nicolaas E.P.; Dasarathy, Srinivasan
<x xml:space="preserve">Abstract</x> Skeletal muscle loss (sarcopenia) is a major clinical complication in alcoholic cirrhosis with no effective therapy. Skeletal muscle autophagic proteolysis and myostatin expression (inhibitor of protein synthesis) are increased in cirrhosis and believed to contribute to anabolic resistance. A prospective study was performed to determine the mechanisms of sarcopenia in alcoholic cirrhosis and potential reversal by leucine. In six well‐compensated, stable, alcoholic patients with cirrhosis and eight controls, serial vastus lateralis muscle biopsies were obtained before and 7 hours after a single oral branched chain amino acid mixture enriched with leucine (BCAA/LEU). Primed‐constant infusion of l‐[ring‐2H5]‐phenylalanine was used to quantify whole‐body protein breakdown and muscle protein fractional synthesis rate using liquid chromatography/mass spectrometry. Muscle expression of myostatin, mammalian target of rapamycin (mTOR) targets, autophagy markers, protein ubiquitination, and the intracellular amino acid deficiency sensor general control of nutrition 2 were quantified by immunoblots and the leucine exchanger (SLC7A5) and glutamine transporter (SLC38A2), by real‐time polymerase chain reaction. Following oral administration, plasma BCAA concentrations showed a similar increase in patients with cirrhosis and controls. Skeletal muscle fractional synthesis rate was 9.63 ± 0.36%/hour in controls and 9.05 ± 0.68%/hour in patients with cirrhosis (P = 0.54). Elevated whole‐body protein breakdown in patients with cirrhosis was reduced with BCAA/LEU (P = 0.01). Fasting skeletal muscle molecular markers showed increased myostatin expression, impaired mTOR signaling, and increased autophagy in patients with cirrhosis compared to controls (P < 0.01). The BCAA/LEU supplement did not alter myostatin expression, but mTOR signaling, autophagy measures, and general control of nutrition 2 activation were consistently reversed in cirrhotic muscle (P < 0.01). Expression of SLC7A5 was higher in the basal state in patients with cirrhosis than controls (P < 0.05) but increased with BCAA/LEU only in controls (P < 0.001). Conclusions: Impaired mTOR1 signaling and increased autophagy in skeletal muscle of patients with alcoholic cirrhosis is acutely reversed by BCAA/LEU. (Hepatology 2015;61:2018‐2029)